2021
DOI: 10.3390/biom12010052
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Association with Ki-67, MCM3 and MT-I/II in Squamous Cell Carcinomas of the Larynx

Abstract: Background: Current studies indicate irisin role in carcinogenesis. The aim of the study was to investigate the expression of irisin in LSCCs and to determine its association with clinicopathological factors, as well as recognized markers of proliferation, i.e., Ki-67 and MCM3,5,7 and MT-I/II proteins. Material and methods: The research material consisted of 140 cases of LSCCs, 57 cases of laryngeal papillomas (BLs) and 14 controls (benign hypertrophic changes). Tissue microarrays were used to perform IHC. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…This may indicate an inhibitory role of irisin in the EMT process of BC cells. Studies by Nowinska et al [ 20 ], Pinkowska et al [ 19 ], and Zhang et al [ 27 ] support our hypothesis. Further studies are warranted to elucidate the mechanism of how irisin affects EMT inhibition and metastasis formation.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This may indicate an inhibitory role of irisin in the EMT process of BC cells. Studies by Nowinska et al [ 20 ], Pinkowska et al [ 19 ], and Zhang et al [ 27 ] support our hypothesis. Further studies are warranted to elucidate the mechanism of how irisin affects EMT inhibition and metastasis formation.…”
Section: Discussionsupporting
confidence: 87%
“…In our previous study [ 20 ], we observed a decrease in irisin levels in non-small cell lung carcinoma (NSCLC) cells from patients with lymph node metastases (N1) compared to those without metastases. We also reported a similar observation in laryngeal squamous cell carcinoma (LSCC) [ 19 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations